Comparison of High-Strength Steel Pipe and H-Shaped Steel in the Strut of a Braced Wall System. Issue 1 (1st January 2017) - Kim, Sangyong; Whang, Seoung-Wook; Lee, Young-Do; Shin, Yoonseok; Kim, Gwang-Hee
Abstract : Excavation work accounts for a high percentage of the total building construction cost. The most widely used method for excavation work in an urban area is a braced wall system with struts or rakers. H-shaped steel, which is the most commonly used component for struts in braced wall systems, has disadvantages such as cost-ineffectiveness and increased work interference associated with narrow strut spacing. Therefore, the use of high-strength steel pipe struts in braced wall systems can be an effective alternative to widening the strut spacing. In this study, the construction costs of a braced wall system using H-shaped steel and a braced wall system made with high strength steel pipe were compared by analyzing the required amounts of materials and the construction costs for four practical cases. All analyzed cases considered a change from H-shaped steel to high strength steel pipe in a design change during the construction stage. The results of this study show that the required amount of materials and the construction costs of a braced wall system with high strength steel pipe were lower than those of a braced wall system with H-shaped steel. Consequently, this study suggests that a high strength steel pipe strut is a more economical alternative than an H-shaped steel strut in braced wall systems for deep excavation work.